Income Inequality, Equality of Opportunity, and Intergenerational Mobility - Miles Corak (Institute for the Study of Labor (IZA), 2013)
Families, labor markets, and public policies all structure a child's opportunities and determine the extent to which adult earnings are related to family background. Cross-country comparisons and the underlying trends suggest that these drivers will most likely lower the degree of intergenerational earnings mobility for the next generation of Americans coming of age in a more polarized labor market, while the substantial rise in the income shares of the top 1 percent, their access to sources of high-quality human capital investment for their children, and the intergenerational transmission of employers and wealth will imply a much higher rate of transmission of economic advantage at the very top.
Keywords: D31; D63; J62; 330; inequality; intergenerational mobility; human capital